OGA-UCT: On-the-Go Abstractions in UCT - Anand, Ankit; Noothigattu, Ritesh; ., Mausam; Singla, Parag (Proceedings of the International Conference on Automated Planning and Scheduling, 2016)
Recent work has begun exploring the value of domain abstractions in Monte-Carlo Tree Search (MCTS) algorithms for probabilistic planning. These algorithms automatically aggregate symmetric search nodes (states or state-action pairs) saving valuable planning time. Existing algorithms alternate between two phases: (1) abstraction computation forcomputing node aggregations, and (2) modified MCTS that use aggregate nodes. We believe that these algorithms do not achieve the full potential of abstractions because of disjoint phases – e.g., it can take a while to recover from erroneous abstractions, or compute better abstractions based on newly found knowledge.In response, we propose On-the-Go Abstractions (OGA), a novel approach in which abstraction computation is tightlyintegrated into the MCTS algorithm. We implement these on top of UCT and name the resulting algorithm OGA-UCT.It has several desirable properties, including (1) rapid use of new information in modifying existing abstractions, (2) elimination of the expensive batch abstraction computationphase, and (3) focusing abstraction computation on important part of the sampled search space. We experimentally compare OGA-UCT against ASAP-UCT, a recent state-of-the-art MDP algorithm as well as vanilla UCT algorithm. We find that OGA-UCT is robust across a suite of planning competition and other MDP domains, and obtains up to 28 % quality improvements.